2023
DOI: 10.2478/logi-2023-0012
|View full text |Cite
|
Sign up to set email alerts
|

Customer Requirements for Public Mass Transport During the COVID-19 Pandemic

Abstract: In today’s rapidly changing business environment, it is important for a company to succeed. This applies to companies that produce goods as well as to those that provide services, and public transport is not different. Nowadays, people prefer individual transport. In the Slovak Republic, individual transport is perceived as an expression of personal prestige and freedom. On the other hand, however, it places a heavy burden on road infrastructure and has a great impact on the environment. In this paper, the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The public avoided crowded spaces, including public transport, due to the fear of contracting the illness. Remote working also contributed to reduced usage of public transport [18]. The ridership statistics and reported findings of previous studies revealed that the primary concern in this research area was the low rate of railway ridership.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The public avoided crowded spaces, including public transport, due to the fear of contracting the illness. Remote working also contributed to reduced usage of public transport [18]. The ridership statistics and reported findings of previous studies revealed that the primary concern in this research area was the low rate of railway ridership.…”
Section: Introductionmentioning
confidence: 76%
“…The COVID-19 pandemic significantly reduced the ridership of the Kuala Lumpur monorail service to 4,226,329 in 2021 and 7,143,534 in 2022 [14]. The movement restriction, Conditional Movement Control Order (CMCO) and Recovery Movement Control Order (RMCO) implemented by governments across the globe to prevent the spread of the virus transmission during the COVID-19 pandemic had a similar impact on public transport performance in other countries, such as Italy [17], Slovakia [18,19], Thailand [20], Bangladesh [21], and others [22]. The public avoided crowded spaces, including public transport, due to the fear of contracting the illness.…”
Section: Introductionmentioning
confidence: 99%